Daridorexant as a new dual orexin receptor antagonist for insomnia - a literature review - Wiktoria Izdebska; Patrycja Sornek; Jakub Stanek; Anna Kaźmierczak; Klaudia Perkowska; Agata Borkowska; Anna Kiełb; Igor Pawlak; Anna Mich; Radosław Ciesielski (Nicolaus Copernicus University in Toruń, 2024)
Introduction and purpose of review: Insomnia is a prevalent disorder responsible for multiple negative effects on human health. Its treatment involves both non pharmacological and pharmacological methods, however many common insomnia medications are recommended not to be used long term. Daridorexant is a new dual orexin receptor inhibitor, recently approved by the EMA for use in the European Union. The aim of this study is to present current knowledge concerning daridorexantsafety, efficacy and general characteristics. Methods: Pubmed database literature review has been performed. Relevant studies regarding daridorexant and insomnia have been assessed. Product characteristics available on EMA, FDA and Idorsia Pharmaceuticals websites have also been inspected. Current state of knowledge: Studies suggest that daridorexant is generally safe and significantly improves the night-time and daytime functioning of people suffering from insomnia, by enabling them to fall asleep in shorter periods of time and stay asleep for longer. It increases time spent in both REM and non-REM phases proportionally and does not disturb physiological sleep architecture. It shows no residual effects in the morning and can be used long-term, with no reduced efficacy and with no signs of physical dependence or withdrawal symptoms. It rarely leads to serious adverse effects and is contraindicated only in a few groups of patients. Conclusions: Daridorexant is a recently approved dual orexin receptor inhibitor with a promising long-term use safety and efficacy profile. As it is a new medication, further investigation concerning the side effects observed over time should be advised.